2009
DOI: 10.1002/lt.21645
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular intrahepatic portosystemic shunt to keep vein open

Abstract: Compared to a surgical shunt, a transjugular intrahepatic portosystemic shunt (TIPS) is a less invasive means of lowering portal venous pressure in patients with cirrhosis experiencing complications of portal hypertension, with relatively low procedure-related morbidity. Presently, the most common indications for TIPS placement are acute variceal bleeding and refractory ascites. The number of other indications is growing, but many are still controversial. We present a patient with partial portal vein thrombosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…[7] The findings of these studies are further supported by report of at least one individual case describing use of TIPS to keep the portal vein open for liver transplantation. [8] Other large studies have confirmed the utility of TIPS in treating PVT in cirrhotic patients without specific intent as a bridge to liver transplantation. In 2011, Luca et al, described 87% patency improvement (complete recanalization in 57%) among 70 patients with nontumoral PVT who underwent TIPS.…”
Section: Discussionmentioning
confidence: 98%
“…[7] The findings of these studies are further supported by report of at least one individual case describing use of TIPS to keep the portal vein open for liver transplantation. [8] Other large studies have confirmed the utility of TIPS in treating PVT in cirrhotic patients without specific intent as a bridge to liver transplantation. In 2011, Luca et al, described 87% patency improvement (complete recanalization in 57%) among 70 patients with nontumoral PVT who underwent TIPS.…”
Section: Discussionmentioning
confidence: 98%
“…Despite advances in surgical techniques, some patients with endstage liver disease and concomitant extensive PVT are still precluded from the transplant list [91,92]. At some centers, [47,63,71,73]. However, the extension of a stent distally into the extrahepatic MPV or the SMV can potentially jeopardize the transplant surgery [93].…”
Section: Tips In Candidates For Liver Transplantationmentioning
confidence: 99%